Living with a disability: A perspective on disability in people living with schizophrenia (PLS) - Raj, Shalila (International Journal of Psychosocial Rehabilitation, 2014)
Schizophrenia is devastating of all mental illness. Disability arising out of schizophrenia is as disastrous as any physical disability. This illness affects all areas of functioning and impairs basic living skills. Disability in carrying out everyday life activities and social func- tioning is the prominent aspect of schizophrenia. It affects the productivity and capability of the person living with it. It prevents people living with schizophrenia from carrying out even the least complex activity. Symptoms are such that it prevents the individual from fo- cusing on any activity. Their involvement in social activities decreases over the period of time. Their participation in community activit- ies tends to be minimal. People living with schizophrenia show a tendency to avoid contact with other people. This is a major reason for complete social isolation and non-active social life. Studies show that medication and psychosocial rehabilitation are helpful in reducing disability. The time, money, and effort required for psychosocial rehabilitation process are the challenges. The data used in this article is part of a larger ethnographic study